Elucidating the biochemical basis of trans‐16:1 fatty acid change in leaves during cold acclimation in wheat. Issue 3 (17th May 2021) - Li, Qiang; Shen, Wenyun; Mavraganis, Ioannis; Wang, Liping; Gao, Peng; Gao, Jie; Cram, Dustin; Li, Yifeng; Liu, Ziying; Fowler, David Brian; Pan, Youlian; Zou, Jitao
Abstract: In plant cells, phosphatidylglycerol (PG) in the chloroplast has a characteristic trans ‐∆3‐hexadecenoic acid (t16:1) at the sn ‐ 2 position. The t16:1 content in wheat leaf tissues decreases during cold treatment, but the significance of this fatty acid compositional change and the underlying biochemical mechanism remains poorly understood. Using a large collection of wheat cultivars displaying a varying capacity of freezing tolerance, we show for the first time under field conditions that this low temperature induced t16:1 change is associated with winter hardiness. To explore the metabolic mechanism responsible for the reduction of t16:1, we performed detailed lipid analysis and comparative transcriptome study with four selected wheat lines under cold acclimation. Our results show that wheat leaf tissues experience a gradual decrease in chloroplast lipid pathway activity during cold acclimation and that the decline in chloroplast lipid synthesis manifests itself in the decrease of t16:1 in PG. Comparative RNA‐seq analyses with leaf tissues further reveal concerted transcriptome shifts indicating a rebalancing of chloroplast and cytosolic lipid synthesis during cold acclimation. Our study, thus, provides mechanistic understanding on chloroplast lipid adjustments as a "molecular ideotype" and the t16:1 change as a specific metabolite marker for screening freezing tolerance in wheat.